A Randomized, Double-Blind, Placebo-Controlled, Phase 1 Trial of Radiopaque Islatravir-Eluting Subdermal Implants for Pre-exposure Prophylaxis Against HIV-1 Infection. (1st April 2023) - Matthews, Randolph P.; Zang, Xiaowei; Barrett, Stephanie E.; Koynov, Athanas; Goodey, Adrian; Heimbach, Tycho; Weissler, Vanessa L.; Leyssens, Carlien; Reynders, Tom; Xu, Zhiqing; Rottey, Sylvie; Vargo, Ryan; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: Islatravir (MK-8591) is a deoxyadenosine analog in development for the treatment and prevention of HIV-1 infection. An islatravir-eluting implant could provide an additional option for pre-exposure prophylaxis (PrEP). Setting: Previous data support a threshold islatravir triphosphate concentration for PrEP of 0.05 pmol/10 6 cells in peripheral blood mononuclear cells. Prototype islatravir-eluting implants were previously studied to establish general tolerability and pharmacokinetics (PKs) of islatravir relative to the threshold level. Methods: In this randomized, double-blind, placebo-controlled, phase 1 trial, a next-generation radiopaque islatravir-eluting implant (48 mg, 52 mg, or 56 mg) or placebo implant was placed for a duration of 12 weeks in participants at low risk of HIV infection. Safety and tolerability, as well as PK for islatravir parent and islatravir triphosphate from plasma and peripheral blood mononuclear cells, were assessed throughout placement and 8 weeks after removal. Results: In total, 36 participants (8 active and 4 placebo per dose arm) were enrolled and completed this study. Implants were generally well tolerated, with no discontinuations due to an adverse event, and no clear dose-dependence in implant-related adverse events. No clinically meaningful relationships were observed for changes in laboratory values, vital signs, or electrocardiogram assessments. Mean islatravir triphosphate levels at day 85 (0.101–0.561 pmol/10 6  cells) were above the PK threshold for all dose levels. Conclusion: Islatravir administered using a subdermal implant has the potential to be an effective and well-tolerated method for administering PrEP to individuals at risk of acquiring HIV-1.